Synthesis of SiO2 Nanoparticle Epoxy Resin Composite and Silicone-Containing Epoxy Resin for Coatings - Shengwen Wang; Yinxiang Qiu (Applied Bionics and Biomechanics)
Due to its unique properties, including strong adhesion force, high heat resistivity, high insulation properties, and strong mechanical properties, epoxy resin is the most commonly used material for a variety of applications, including adhesives, electronic devices for coatings, and somewhere as a matrix for reinforcement of composites as a fiber network. To boost their properties, different other materials are also inserted in their structure and made its composites; silicon is one of them. Corrosion is serious for marine equipment and causes economic loss. To overcome such issues, different types of coating materials are developed. In this review, current methods for coatings of different materials using a silicon dioxide epoxy nanocomposite are discussed in diversity with the currently followed synthetic routes for the preparation of nanosilica epoxy composites and enhanced properties.